Development of Yoghurt Incubator for Small-Scale Production using PIC16F877A Microcontroller (Global Journal of Science Frontier Research, 2016)
The largest population of livestock in Africa is found in Ethiopia. The country produces about 3.2 billion litters of milk annually from 10 million milking cows. Yogurt processing is one of the ways to prolong the shelf life of milk. Thus a low-cost yogurt incubator suitable for small scale production which was equipped with a microcontroller was developed. The main components of the incubator include the microcontroller and temperature sensor, alarm circuit, power supply circuit, and the embedded program. The incubation chamber was made of a locally available ½ inch ordinary plywood. The components were assembled and installed after the incubation chamber was constructed. The operating temperature of the incubator was set at 42 o C (±1 o C). The incubator was tested using one litter of pasteurized cow's milk inoculated with Lactobacillus bacteria. The inoculated milk was placed in bottles and incubated for 24 hours. Results of the sensory test showed that the incubator produced a good quality yogurt comparable to that being sold in the area.
Keywords: microcontroller; incubator; yoghurt; temperature sensor; relay driver; relay; heater and buzzer